PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2018)
Human Resources is an important property by a company. Having a high performance, attitude and motivation of human resources would support the main goal of the company. Reaching the main goal of the company would make the company is able to survive in the middle of the higher of minimum wage in Indonesia, especially in Tanjungpinang Island. The main goal of the research is to know that motivation and performance coaching make a significant influence toward employee PT. Mandiri Tunas Finance even in partial or simultaneous. Population of the research is all of the employee PT. Mandiri Tunas Finance, which is count 147 people, from this population the researcher will choose sample that used as respondent in this research. Then, the researcher used simple random sample in this research. By using Slovin formula, then the researcher get 108 people as sample. Method of data accumulation is by using answer sheet. The data analysis is using double linier regression by using SPSS software. Result of the research shows that by giving motivation and job coaching was influential toward employee performance even partial or simultaneously, while the percentage of determination coefficient (R2) was 25.30%. it means that performance was influenced by motivation and coaching in the amount of 25.30%, while the others influence by others revealed variables